A Japanese family with a variant of Gerstmann-Sträussler-Scheinker disease. Issue 5 (May 1997) - Tanaka, Y; Minematsu, K; Moriyasu, H; Yamaguchi, T; Yutani, C; Kitamoto, T; Furukawa, H
Abstract : OBJECTIVE: A new variant of Gerstmann-Sträussler-Scheinker disease (GSS) was reported, which had a substitution of glutamate to lysine at codon 219 (E219K) in addition to a P102L mutation on the same allele of the PrP gene. However, clinical features were not detailed and pathological studies were not done. Unusual clinical, neuroradiological, and pathological findings are reported for these patients. METHODS AND RESULTS: Clinical presentations of the patients in the same family were variable; progressive dementia with minimal ataxia in some patients but ataxia without dementia in others. PET studies with 18F-2-fluoro-2-deoxyglucose (FDG) disclosed a relative decrease of FDG uptake in bilateral temporoparietal cortices of a patient with dementia, but in the cerebellar cortices in a patient with ataxia. At necropsy, a patient with dementia had multicentric and diffuse plaques stained with PrP antiserum, but not with haematoxylin and eosin or Congo red, in the cerebral and cerebellar cortices. CONCLUSION: Neurological and neuropathological features in the patients were atypical of the classic form of GSS with P102L mutation. The absence of Congo red staining prion protein plaques is probably attributable to E219K polymorphism on the same allele of the PrP gene.